Properties of endotracheal tubes reprocessed by two procedures - Elisa Elisa; S. H. Purwanto; A. T. Aman; Y. Pranoto; Kusmono Kusmono (Indonesian Pediatric Society, 2011)
Background Reusing endotracheal tubes (EITs) has beenÂ performed in Indonesia with no evidence of its safety.Â Objective To evaluate sterility, as wellÂ as the mechanical, surface, and matrix properties of reused EITsÂ following 2 different reprocessing procedures.Methods Reused EITs were cleaned and disinfected, thenÂ sterilized by ethylene oxide gas sterilization (group A) or dry heatÂ sterilization (group B). New EITs were used as the standardÂ for comparison. Microbes were identified and microbial countsÂ were determined as colony forming units (CFUs). EvaluationÂ of mechanical properties was perfonned by a Universal TestingÂ machine. All samples underwent tensile and compression tests.Load defonnation curves were recorded from F max and strain at FÂ max. Microstructure analysis was done using Xô€…ray photoelectronÂ spectroscopy (XPS), scanning electron microscopy (SEM), andÂ energy-dispersive X-ray spectroscopy (EDX).Results Positive cultures of commensal bacteria were found inÂ 2/12 samples in group A, and 5/17 samples in group B. T hereÂ was no statistically significant difference between them (P =0.07). Pseudomonas aeruginosa or other common pathogens wereÂ not found. Samples from both groups showed equal flaccidity,Â compared to the standard. Surface microstructure analysis ofÂ reused EITs 'With XPS and EDX showed degradation of the matrixcomponent. SEM analysis detected some large particles andÂ fissures. EDX analysis on the large particles detected sodium andÂ calcium signals. Altogether, signs of contamination and materialÂ damage were very strong.Conclusion Both reprocessing methods of reused EITs gaveÂ comparable results on sterility and mechanical behavior, butÂ reprocessing may cause decreased surface and matrix quality.Â